Intermediate doses of low-molecular-weight heparin for the long-term treatment of pregnancy thromboembolism. A systematic review - Gándara, Esteban; Carrier, Marc; Rodger, Marc A. (Thrombosis and Haemostasis, 2014)
Note: The contact information for Drs. Gandara and Carrier is the same as for Dr. Rodger. Their e-mail addresses are egandara@ohri.ca and mcarrier@ohri.ca, respectively.